The Marausa Wreck, Sicily: interim report on a boat built in the Western Imperial Roman tradition. (8th July 2016) - Tiboni, Francesco; Tusa, Sebastiano
Abstract : In 1991, the wreck of a late 3rd–early 4th century AD Roman merchant vessel was discovered on the west coast of Sicily that had carried North African amphora, tubuli, and other ceramics. The hull was dismantled and raised in 2011, including a keel hook‐scarfed to stem and sternposts, 39 pegged mortise‐and‐tenon joined planks, 43 frames with an irregular pattern of floor‐timbers, half‐timbers, and futtocks fastened to the planking with treenails and copper nails, sister‐keelsons and evidence of two stringers, 36 ceiling strakes, and the base of a bilge pump. Many repairs are indicated. The fairly flat bottom and round bilges, mortise‐and‐tenons, sister‐keelsons and lack of a coherent framing pattern, place the boat in the Western Imperial tradition.